Oral squamous cell carcinoma involving a blue cell nevus in the palate - Barnabé, Luan Éverton Galdino; Paz, Alexandre Rolim; Gomes, Daliana Queiroga Castro; Pereira, Jozinete Vieira; Nonaka, Cassiano Francisco Weege; Alves, Pollianna Muniz (Journal of Oral Diagnosis, 2017)
Introduction: Squamous Cell Carcinoma (SCC) is the most common malignant neoplasm of the oral cavity; however, there is no report in the literature of SCC involved with blue nevus. Case report: We report the case of a patient, a 54-year-old woman who exhibited a brownish spot associated with whitish area, surrounded by a hyperemic area in the soft palate. After an incisional biopsy and histopathological analysis, the presence of invasive squamous cell carcinoma was shown, in addition, in other fragment, to the presence of fusiform cells disposed parallel to the epithelium, exhibiting intense brownish cytoplasmic pigments. Immunohistologically, the neoplastic epithelial cells demonstrated intense immunoexpression for the anti-pan Cytokeratin antibody, while the fusiform cells showed strong immunopositivity for the anti-S-100 and anti-Melan-A antibodies, and weak immunomarking for anti-HMB-45. Based on the microscopic findings described, the final diagnosis was Oral Squamous Cell Carcinoma (OSCC) involving a blue cell nevus. Conclusion: Therefore, we sought to relate the first case of involvement of OSCC and blue cell nevus, up to the present time.